(untitled) (Journal of Enam Medical College, 2016)
Background: Preterm birth is associated with variable degree of brain injury and adverse neurodevelopmental outcomes. Therefore, screening of these infants is required to assess further neurodevelopmental abnormalities. Cranial ultrasound finding has been a predictor of outcome in this population. Objective: The present study was carried out to find cranial ultrasound abnormalities in preterm neonates to aid in screening at risk infants for long term neurodevelopmenal impairment. Materials and Methods: This observational study was conducted in Dhaka Shishu (Children) Hospital from October 2011 to March 2012. Total 103 preterm neonates who met the inclusion criteria were enrolled in the study. The neonates underwent cranial ultrasound (cUS) scan just after admission and before discharge for screening at risk infants. Results: Total 103 neonates were enrolled with mean age of 7.67 days in neonates with normal cUS findings and 7.23 days in neonates with abnormal cUS findings. Mean gestational age was 31.94 weeks in neonates with normal cUS and 31.85 weeks in neonates with abnormal cUS findings with mean weight 1.83 and 1.81 kg respectively. Among the neonates, 64 (62.1%) were males and 39 (37.9%) were females. Before discharge, out of 103 preterm neonates, 56 (54.3%) had normal cUS and 47 (45.7%) had abnormal cUS findings of which 22 (21.4%) had cerebral edema, 17 (16.5%) IVH and 8 (7.8%) had ventricular dilatation. Conclusion: Routine cranial ultrasound scanning of preterm neonates may aid in identifying at risk infants for long term neurodevelopmental impairments. J Enam Med Col 2016; 6(1): 28-32